An Analysis of Foreign Capital Inflows, Institutional Quality and Economic Performance in SAARC Countries (Journal of Asian Development Studies, 2024)
This paper is interested in seeing and exploring the relationship between foreign capital inflows, the quality of domestic institutions, and economic performance. The paper focuses on SAARC economies and utilizes data from 1996-2020. Our results show that foreign aid and economic growth of SAARC countries were positive results from all four techniques we used in our study. For imports, we got positive results in pooled least squares, whereas we got a negative impact of imports on the economic growth of SAARC countries in the other three techniques. We got the negative and insignificant impact of FDI in pooled least squares and generalized least squares, whereas we got the positive and significant impact of FDI in two stages of least squares. We learned about the negative and significant effects of debt on the economic growth of SAARC countries through all four techniques we have used. Regarding remittances, we got mixed results. Regarding institutions, we got institutions' negative and considerable impact on the economic development of SAARC countries in all specifications. Our results have important policy implications for SAARC economies.